Numerical simulation of sea breeze in south Andamans (MAUSAM, 1991)
The air flow over the south Andaman island is simulated using a three dimensional numerical meso-scale model. Port Blair observations are used as initial data. The surface orography, soil moisture soil albedo variations and vegetations effects are included in the model. The combined effect of these factors on the development of sea/land breeze circulations is obtained quantitatively. The model simulated results are compared with the available observations. The principal results obtained are : (1) The meso-scale circulations induced by the differential heating of the island were intensified by topography. (2) The ground vegetative cover trans- port higher amount of turbulent heat fluxes: to the atmosphere and the meso-circulations appeared with higher intensities. (3) If we Include the lateral variations of flux with topographic and coastal asymmetries the induced meso-scale circulations appeared with different intensities along meridional direction and the inland penetration distances varied in y direction. The maximum Inland penetration of sea breeze was seen, where the inland was widest and terrain height was maximum. Stronger sea breeze was simulated over the central/northern parts of the island.